Water-soluble polymer solid electrolyte as well as preparation method and application thereof
By using water-soluble block polymers and metal salts to prepare water-soluble polymer solid electrolytes, the shortcomings of existing solid electrolytes in electrochemical performance, cost and environmental adaptability are solved, and a high-performance and environmentally friendly solid battery electrolyte is achieved.
Patent Information
- Application Number
- CN202411856438.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The existing solid-state electrolytes have defects in electrochemical performance, preparation cost, environmental adaptability and contamination, which limits the development of solid-state batteries.
The slurry is prepared using water-soluble block polymer, metal salt and fast ion conductor, and scraped onto the porous fiber skeleton and dried to prepare a water-soluble polymer solid electrolyte.
It realizes a low-cost, environmentally friendly, and suitable for industrial production, with high ionic conductivity and interface stability, and improves the performance and safety of solid lithium and sodium batteries.
Smart Images

Figure CN119674191A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and more specifically relates to a water-soluble polymer solid electrolyte and a preparation method and application thereof. Background Art
[0002] With the continuous advancement of clean energy-related technologies, industries such as portable electronics and electric vehicles have developed rapidly. Various fields have also begun to use electricity to replace conventional energy. Ordinary lithium-ion batteries have safety hazards such as flammability and explosion. Solid-state batteries have gradually stood out because of their relatively safe characteristics. In solid-state batteries, solid electrolytes play an extremely important role, and the characteristics of solid electrolytes directly determine the performance of the battery. Solid electrolytes are divided into inorganic solid electrolytes and polymer solid electrolytes, but they all have more or less defects, such as poor electrochemical performance, high preparation cost, poor adaptability to the environment, and greater environmental pollution during the preparation of electrolytes. These shortcomings restrict the development of solid-state batteries.
[0003] How to provide a water-soluble, environmentally friendly polymer composite solid electrolyte to overcome the problems existing in the solid electrolyte in the prior art has become an issue that technicians in this field urgently need to solve. Summary of the invention
[0004] The purpose of the present invention is to provide a water-soluble polymer solid electrolyte and its preparation method and application, and more specifically to provide a water-soluble environmentally friendly polymer composite solid electrolyte, its preparation method and solid-state lithium and sodium batteries to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a water-soluble polymer solid electrolyte, the steps comprising:
[0007] The water-soluble block polymer, metal salt and fast ion conductor are prepared into slurry, which is then coated on a porous fiber skeleton and dried to form a film to obtain the water-soluble polymer solid electrolyte.
[0008] Furthermore, the water-soluble block polymer is an amphiphilic block copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene (PEO-PPO-PEO).
[0009] Optionally, the amphiphilic block copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene is selected from F127, F68, F88 or P85.
[0010] Furthermore, the metal salt is selected from one of lithium nitrate, sodium nitrate, lithium perchlorate, sodium perchlorate, lithium chloride and sodium chloride.
[0011] Furthermore, the fast ion conductor is selected from one of Li-β″-Al2O3 (LAO), Na-β″-Al2O3, LLZO and LAGP.
[0012] Furthermore, the mass ratio of the water-soluble block polymer to the metal salt is 10:1-3.
[0013] Furthermore, the mass ratio of the water-soluble block polymer to the fast ion conductor is 10:1-7.
[0014] Furthermore, the drying and film-forming temperature is 60-120°C.
[0015] Furthermore, the solvent used in the slurry is water.
[0016] The second technical solution of the present invention is to provide a water-soluble polymer solid electrolyte, which is prepared by the above-mentioned preparation method.
[0017] The third technical solution of the present invention is to provide an application of the above-mentioned water-soluble polymer solid electrolyte in a solid-state battery.
[0018] Optionally, the solid-state battery is a solid-state lithium battery or a solid-state sodium battery.
[0019] A fourth technical solution of the present invention is to provide an electrochemical device, wherein the electrochemical device comprises the above-mentioned water-soluble polymer solid electrolyte.
[0020] Optionally, the electrochemical device includes a solid-state lithium battery, a solid-state sodium battery, a supercapacitor, a lithium-sulfur battery or a metal-air battery.
[0021] The water-soluble polymer solid electrolyte prepared by the present invention can be used in supercapacitors to improve the energy density and power density of supercapacitors, while improving their cycle stability and safety; it can be used in lithium-sulfur batteries to help solve the polysulfide shuttle effect in lithium-sulfur batteries, thereby improving the cycle life and energy density of the batteries, and can also prevent the formation of lithium dendrites and increase the safety of the batteries; it can be used in metal-air batteries to help control gas exchange and improve battery efficiency, enhance battery safety, and reduce the occurrence of side reactions.
[0022] The present invention discloses the following technical effects:
[0023] The present invention uses water as a solvent, a water-soluble polymer, a metal salt and an ion conductive filler to prepare a slurry, and then prepares a water-soluble polymer solid electrolyte, which has low cost, no organic pollutant emissions, good environmental protection, and is prepared under air conditions without harsh preparation conditions, and is suitable for industrial production. At the same time, the prepared solid electrolyte has the characteristics of high ionic conductivity and high interface stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0025] Figure 1 (a) is the SEM image of F127 / LiNO3; (b) is the SEM image of F127-LAO; (c) is the Al element energy spectrum of F127-LAO; (d) is the cross-sectional SEM image of F127-LAO.
[0026] Figure 2 (a) is the physical picture of PE, F127 / LiNO3 and F127-LAO before heat treatment; (b) is the physical picture of PE, F127 / LiNO3 and F127-LAO after heat treatment at 130℃ for 10min; (c) is the physical picture of PE, F127 / LiNO3 and F127-LAO after heat treatment at 130℃ for 30min; (d) is the TG curve of F127 / LiNO3 and F127-LAO; (e) is the DSC curve of F127-LAO.
[0027] Figure 3 (a) is the EIS spectra of F127 / LiNO3 and F127-LAO; (b) is the ionic conductivity of F127 / LiNO3 and F127-LAO at different temperatures; (c) is the steady-state polarization curve of F127-LAO, and the inset shows the Nyquist impedance spectrum of the Li / F127-LAO / Li battery before and after polarization; (d) is the linear sweep voltammogram of F127 / LiNO3 and F127-LAO.
[0028] Figure 4 The figures show the electrochemical performances of LFP / F127 / LiNO3 / Li and LFP / F127-LAO / Li SE batteries; (a) is the EIS curve; (b) is the cycle performance; (c) is the charge and discharge curves of LFP / F127-LAO / Li battery at different current densities; (d) is the high rate performance curve; and (e) is the rate performance curve.
[0029] Figure 5Characterization diagrams of the solid electrolytes prepared in Example 2 and Comparative Example 2; wherein, (a) is a SEM image of the surface of Comparative Example 2; (b) is a SEM image of F127-10% Na-β″-Al2O3; (c) is a SEM image of F127-20% Na-β″-Al2O3; (d) is a SEM image of F127-30% Na-β″-Al2O3; (e) is a SEM image of F127-40% Na a) SEM image of F127-β″-Al2O3; (f) energy spectrum of Al element on the surface of F127-20% Na-β″-Al2O3; (g) actual image of F127-20% Na-β″-Al2O3; (h) SEM image of the cross section of F127-20% Na-β″-Al2O3; (i) energy spectrum of Al element in the cross section of F127-20% Na-β″-Al2O3.
[0030] Figure 6 (a) is the stress-strain curve of PE film, F127-20% Na-β″-Al2O3, F127-30% Al2O3 and F127-80% Na-β″-Al2O3; (b) is the changes of Example 2 and PE film at different temperatures and holding time; (c) is the TG curve of F127-NaClO4, F127-30% Al2O3, F127-20% Na-β″-Al2O3; (d) is the DSC curve of F127-NaClO4, F127-30% Al2O3, F127-20% Na-β″-Al2O3.
[0031] Figure 7 (a) is the EIS spectra of Example 2, Comparative Example 2 and F127-30% Al2O3; (b) is the ionic conductivity of Example 2 and Comparative Example 2; (c) is the linear sweep voltammogram of Example 2, Comparative Example 2 and F127-30% Al2O3; (d) is the steady-state polarization curve of F127-20% Na-β″-Al2O3, and the inset is the Nyquist impedance spectrum of the Na / F127-20% Na-β″-Al2O3 / Na battery before and after polarization.
[0032] Figure 8 (a) is the EIS curve of the NVP / electrolyte / Na battery prepared by Example 2, Comparative Example 2 and F127-30%Al2O3; (b) is the cycle performance of the NVP / electrolyte / / Na battery prepared by Example 2, Comparative Example 2 and F127-30%Al2O3; (c) is the charge and discharge curve of the NVP / F127-20%Na-β″-Al2O3 / Na battery; (d) is the rate performance curve of the NVP / electrolyte / Na battery prepared by Example 2 and Comparative Example 2.
[0033] Fig. 9(a) shows the constant current cycle curves of F127-NaClO4, F127-30% Al2O3 and F127-20% Na-β″-Al2O3 membrane Na symmetric batteries and the actual surface image of the sodium sheet after cycling; (b) shows the critical current density test of F127-20% Na-β″-Al2O3 membrane Na symmetric battery when the current density is increased stepwise; (c) shows the step size of the current increase of 0.05 mA cm -2 Symmetrical Na cell with F127-20% Na-β″-Al2O3 membrane at current density of 0.1 to 0.8 mA / cm 2 The static electricity cycle. DETAILED DESCRIPTION
[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0035] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0039] The "room temperature" and "normal temperature" referred to in the specific embodiments of the present invention are generally 20-30°C.
[0040] The raw materials and reagents used in the specific embodiments of the present invention are all commercially available products.
[0041] Example 1
[0042] Preparation of water-soluble polymer solid electrolyte:
[0043] 1 g F127 and 0.1 g lithium nitrate were dissolved in 3.5 g deionized water, and then 0.5 g Li-β″-Al2O3 was added, and the mixture was placed in a degassing machine for 3 min, followed by ultrasonic vibration for 10 min, and then placed on a magnetic stirrer and stirred for 5 h to obtain a uniform slurry;
[0044] Pour part of the slurry onto a glass plate, and apply it evenly on the glass plate with a scraper with a gap of 150 μm. Place a 9 μm PE skeleton on the slurry just applied, and then pour the remaining slurry onto the PE skeleton, and apply it evenly with a scraper with a gap of 200 μm. Then, dry it in a forced air drying oven at 80°C for 12 h, and vacuum dry it at 100°C for 12 h to obtain a water-soluble polymer solid electrolyte, recorded as F127-LAO, which is stored in an argon glove box for future use.
[0045] Comparative Example 1
[0046] Compared with Example 1, the difference is that Li-β″-Al2O3 is not added, and the prepared solid electrolyte is recorded as F127 / LiNO3.
[0047] Figure 1 (a) is the SEM image of F127 / LiNO3; (b) is the SEM image of F127-LAO; (c) is the Al element energy spectrum of F127-LAO; (d) is the cross-sectional SEM image of F127-LAO. As can be seen from the figures, in (a), the holes on the surface of the PE membrane are filled with polymer, and the skeleton is not visible. The small picture (the blue part on the left) is a real picture. The surface of the electrolyte membrane becomes transparent, indicating that the polymer and lithium salt have been polymerized; in (b), it can be seen that the filler is wrapped by the polymer and evenly distributed on the surface of the PE membrane. The small picture (the white part on the left) is a real picture. Due to the addition of LAO filler, the transparent electrolyte membrane turns white; (c) is the Al element EDS energy spectrum of F127-LAO. It is found that there are many LAO particles evenly distributed on the surface of the PE membrane; in (d), it can be seen that LAO particles have penetrated the middle of F127-LAO, and the thickness of the membrane is about 23μm. Due to the presence of LAO particles, the ion transport performance is improved, which is beneficial for lithium ions to shuttle in the electrolyte.
[0048] Glass transition temperature (Tg) and thermal stability are important indicators for evaluating electrolyte performance. From a macroscopic perspective, the impact of temperature changes on electrolyte membranes, such as Figure 2shown.
[0049] Figure 2 (a) is the physical picture of PE, F127 / LiNO3 and F127-LAO before heat treatment, (b) is the physical picture of PE, F127 / LiNO3 and F127-LAO after heat treatment at 130℃ for 10min, (c) is the physical picture of PE, F127 / LiNO3 and F127-LAO after heat treatment at 130℃ for 30min, (d) is the TG curve of F127 / LiNO3 and F127-LAO, and (e) is the DSC curve of F127-LAO. (From left to right in (a) to (c) are PE, F127 / LiNO3 and F127-LAO) As can be seen from the figure, the diameters of PE, F127 / LiNO3 and F127-LAO that have not been heat treated in (a) are the same, all 19 mm; in (b), after heat treatment at 130°C for 10 min, PE shrinks severely at high temperature, while the sizes of F127 / LiNO3 and F127-LAO do not change much; in (c), when the heat treatment time reaches 30 min, the size of PE shrinks to half of its initial size, F127 / LiNO3 shrinks slightly, and F127-LAO does not change; in (d), there is a slight weight loss of about 8.6% from room temperature to 250°C. This is because the solvent deionized water in the electrolyte is not completely dried, resulting in the evaporation of the solvent when the temperature rises. F127 / LiNO3 CSE begins to decompose at about 230°C, while F127-LAO The initial decomposition temperature of CSE is about 250°C, and the mass loss at 500°C is about 80.66%, with the residual weight being LAO and lithium salt, which indicates that F127-LAO CSE has good thermal stability at high temperatures; the Tg and Tm values of F127-LAO in (e) are -46.8°C and 54.3°C, respectively, indicating that F127 can be used as a polymer in the preparation of electrolytes.
[0050] Figure 3 (a) is the EIS spectra of F127 / LiNO3 and F127-LAO; (b) is the ionic conductivity of F127 / LiNO3 and F127-LAO at different temperatures; (c) is the steady-state polarization curve of F127-LAO, and the inset shows the Nyquist impedance spectrum of the Li / F127-LAO / Li battery before and after polarization; (d) is the linear sweep voltammogram of F127 / LiNO3 and F127-LAO. Electrochemical impedance spectroscopy (EIS) is used to study the ionic conductivity of various electrolytes. It can be seen from the figure that the ionic conductivity of F127 / LiNO3 is 1.2×10 -4 S cm -1 , while F127-LAO with added LAO has a higher room temperature ionic conductivity, which can reach 6.4×10 -4 S cm-1 By comparison, it can be found that after adding an appropriate amount of LAO, the F127-LAO composite solid electrolyte can produce more free Li + , thereby increasing the ionic conductivity ( Figure 3 (a) in the figure); in the temperature range of 20 to 80 °C, the ionic conductivity of F127 / LiNO3 and F127-LAO is as follows Figure 3 As shown in (b), as the temperature gradually increases, the ionic conductivity also increases. It can be seen that the increase in temperature can promote the free Li + In addition, the activation energy was calculated by linearly fitting the slope of the ionic conductivity data at different temperatures. The results showed that the presence of LAO reduced the activation energy of lithium ion migration and provided a channel for the transport of lithium ions, which also explained the increase in ionic conductivity. (c) The polarization curve of F127-LAO and the impedance spectrum before and after polarization, the ion migration number corresponding to F127-LAO is 0.60, and the results show that the addition of LAO helps to enhance the Li + (d) shows the linear sweep voltammetry (LSV) curves of F127 / LiNO3 and F127-LAO. Compared with F127 / LiNO3 without LAO, the presence of LAO increases the electrochemical window of CSE film from 4.4 V to above 4.6 V without decomposition, further indicating that the addition of LAO makes F127-LAO have a wider electrochemical window to adapt to the use of high-voltage positive electrode.
[0051] Figure 4 The electrochemical performance of LiFePO4(LFP) / F127 / LiNO3 / Li and LFP / F127-LAO / Li batteries, where (a) is the EIS curve, (b) is the cycle performance, (c) is the charge and discharge curves of the LFP / F127-LAO / Li battery at different current densities, (d) is the high rate performance curve, and (e) is the rate performance curve. As can be seen from the figure, the battery impedance without LAO filling in (a) is the highest, while the battery impedance filled with LAO is greatly reduced, and the corresponding ion conductivity is also improved; the high rate performance test of LFP / F127 / LiNO3 / Li and LFP / F127-LAO / Li batteries is shown in the figure. Figure 4 As shown in (b), the discharge specific capacities of the LFP / F127-LAO / Li battery at current densities of 0.1C, 0.2C, 0.3C, 0.5C and 1C are 148, 140, 137.7, 127 and 106 mAh g, respectively. -1When the cycle returns to 0.1C, the specific capacity returns to the initial value, indicating that the battery has good reversible stability; (c) shows the change of the charge and discharge platform of the battery at different current densities, and the charge and discharge curves show the typical oxidation / reduction reaction platform of the LFP electrode; try to test the performance of the battery with a higher current density, such as Figure 4 As shown in (d) in the figure, the battery with LAO filler can show better rate performance under fast charge and discharge conditions, while the battery without LAO has a significant decrease in battery specific capacity under 2C conditions. It can be seen that the presence of LAO greatly improves the rate performance, which further illustrates that Li-β″-Al2O3 filler plays an important role in improving the electrochemical performance of batteries, and also shows that the ability to inhibit lithium dendrites is a key issue in stabilizing the electrolyte / electrode interface; the cycle performance and Coulomb efficiency at a rate of 0.5C are shown in Figure 2. Figure 4 As shown in (e), the initial specific capacity of the LFP / F127 / LiNO3 battery without LAO is similar, but the specific capacity decays rapidly with the increase of current density. However, the LFP / F127-LAO / Li battery containing LAO exhibits better cycle performance with an initial specific capacity of 155.7 mAh g -1 After 200 cycles of charge and discharge, the capacity retention rate is 80%, while the LFP / F127 / LiNO3 / Li battery decays faster because of the lack of LAO, which cannot inhibit the growth of lithium dendrites in time, resulting in the continuous consumption or decomposition of lithium dendrites and added liquid electrolyte during the cycle, causing the interface to be destroyed, and ultimately leading to rapid decay of specific capacity.
[0052] Through Example 1 and Comparative Example 1, the present invention combines F127, low-cost lithium salt lithium nitrate and fast ion conductor LAO to successfully prepare F127-LAO, realize the preparation of electrolyte in the air, overcome the problem of conventional electrolytes being afraid of water, and successfully reduce the preparation cost, and finally show excellent electrochemical performance. And because the solvent is water, the pollution to the environment is reduced, the added LAO accelerates the migration speed of lithium ions, and the use of lithium nitrate as a lithium salt reduces the cost while providing nitrate ions that react with lithium sheets to generate Li3N to inhibit lithium dendrites. The ionic conductivity of F127-LAO electrolyte at room temperature is 6.4×10 -4 S cm -1 , the electrochemical window is 4.5V, LAO particles react with lithium metal in the negative electrode to form Li-Al-O layer, which not only promotes Li + The interface transport and uniform deposition of Li can also inhibit the growth of Li dendrites. This provides the possibility for the commercial production of safe and stable CSE films and opens up their practical application in solid-state lithium batteries.
[0053] Example 2
[0054] Preparation of water-soluble polymer solid electrolyte:
[0055] 1 g F127 and 0.2 g sodium perchlorate were dissolved in 3.5 g deionized water, and then 0.1 g, 0.2 g, 0.3 g or 0.4 g Na-β″-Al2O3 were added, and the mixture was placed in a degassing machine for 3 min, followed by ultrasonic vibration for 10 min, and then stirred on a magnetic stirrer for 5 h to obtain a uniform slurry;
[0056] Pour part of the slurry onto a glass plate, and apply it evenly on the glass plate with a scraper with a gap of 150 μm. Place a 9 μm PE skeleton on the slurry just applied, and then pour the remaining slurry on the PE skeleton, and apply it evenly with a scraper with a gap of 200 μm. Then, dry it in a forced air drying oven at 80°C for 12 h, and vacuum dry it at 100°C for 12 h to obtain a water-soluble polymer solid electrolyte, recorded as F127-10% Na-β″-Al2O3, F127-20% Na-β″-Al2O3, F127-30% Na-β″-Al2O3, and F127-40% Na-β″-Al2O3, and store them in an argon glove box for future use.
[0057] Comparative Example 2
[0058] Compared with Example 2, the difference is that Na-β″-Al2O3 is not added, and the prepared solid electrolyte is recorded as F127-NaClO4.
[0059] Comparative Example 3
[0060] Compared with Example 2, the difference is that Na-β″-Al2O3 is replaced by 0.3 g Al2O3, and the prepared solid electrolyte is recorded as F127-30% Al2O3.
[0061] Comparative Example 4
[0062] Compared with Example 2, the difference is that the amount of Na-β″-Al2O3 added is 0.8 g, and the prepared solid electrolyte is recorded as F127-80% Na-β″-Al2O3.
[0063] Figure 5Characterization diagrams of the solid electrolytes prepared in Example 2 and Comparative Example 2, wherein (a) is a SEM image of the surface of Comparative Example 2, (b) is a SEM image of F127-10% Na-β″-Al2O3, (c) is a SEM image of F127-20% Na-β″-Al2O3, (d) is a SEM image of F127-30% Na-β″-Al2O3, and (e) is a SEM image of F127-40% Na a) SEM image of F127-β″-Al2O3, (f) energy spectrum of Al element on the surface of F127-20% Na-β″-Al2O3, (g) actual image of F127-20% Na-β″-Al2O3, (h) SEM image of the cross section of F127-20% Na-β″-Al2O3, (i) energy spectrum of Al element in the cross section of F127-20% Na-β″-Al2O3. As can be seen from the figure, in (a), it can be observed that the holes on the surface of the PE membrane skeleton are filled with polymer, and the skeleton is not visible; in (b) to (e), it can be seen that the Na-β″-Al2O3 filler is wrapped by the polymer and evenly distributed on the surface of the PE membrane; in (g), it can be seen that the transparent electrolyte membrane becomes white due to the addition of Na-β″-Al2O3 filler, resulting in a certain degree of roughness, but at low content, the ceramic particles are not enough to form a continuous transmission path, and at high content, the polymer in CSE cannot completely fill the pores between the particles, which is why they have higher impedance. In contrast, F127-20% Na-β″-Al2O3 has a more uniform and dense structure, the Na-β″-Al2O3 particles are uniformly and continuously adhered together, and the pores are fully filled with polymers; EDS mapping of the Al element in (f) and (i) further proves that F127-20% Na-β″-Al2O3 CSE has a relatively uniform structure. The interior of the electrolyte membrane has been infiltrated by Na-β″-Al2O3 particles. The uniform dispersion of inorganic fillers and low molecular weight polymers is conducive to improving the performance of the composite electrolyte membrane.
[0064] Figure 6(a) is the stress-strain curve of PE film, F127-20% Na-β″-Al2O3, F127-30% Al2O3 and F127-80% Na-β″-Al2O3, (b) is the changes of Example 2 and PE film at different temperatures and holding time, (c) is the TG curve of F127-NaClO4, F127-30% Al2O3, F127-20% Na-β″-Al2O3, (d) is the DSC curve of F127-NaClO4, F127-30% Al2O3, F127-20% Na-β″-Al2O3. The poor mechanical properties of solid electrolyte films can lead to battery safety problems. As can be seen from the figure, the strain of the electrolyte membrane with 20% Na-β″-Al2O3 filler added in (a) reaches 90MPa and the stress reaches 35%. It can be seen that the electrolyte membrane has good mechanical strength. At high content, the mechanical strength of the electrolyte membrane with 80% Na-β″-Al2O3 filler added is reduced. In contrast, the electrolyte membrane has stronger flexibility at low content. Glass transition temperature (Tg) and thermal stability are important indicators for evaluating electrolyte performance. In practical applications, the inability of the electrolyte film to maintain its original shape at high temperature may cause a short circuit in the sodium battery. From a macroscopic point of view, temperature changes have a certain impact on the electrolyte membrane. (b) is a physical picture of Example 2 and PE membrane after heating at room temperature, 130°C for 30 min, 150°C for 30 min, and 150°C for 3 h. The original diameter is 19 mm. It can be seen that different electrolyte membranes show certain changes after heating in the oven. The pure PE membrane changes most significantly, while the size of F127-Na-β″-Al2O3 does not change much. When the heating time is increased to 30 minutes, the size of the pure PE membrane shrinks to half of the initial size, the electrolyte membrane with low-content filler is slightly reduced, and the electrolyte membrane with high-content filler is unchanged, indicating that the addition of fillers improves the heat resistance of the electrolyte and better adapts to high-temperature environments. The electrolyte membrane can also maintain its original shape at high temperatures, which is very useful in practical applications of batteries. It has great practical value and improves safety. (c) From room temperature to 250°C, the solvent deionized water in the F127-30% Al2O3 and F127-NaClO4 electrolytes was not completely dried and absorbed moisture from the air, resulting in a weight loss of about 9.6%. The decomposition of F127-NaClO4 began at about 200°C, the decomposition of F127-30% Al2O3 began at about 210°C, and the initial decomposition of F127-20% Na-β″-Al2O3 was around 220°C. Based on the residual weight of Na-β″-Al2O3 and sodium salt, the mass loss at 500°C was about 79.3%. This shows that F127-20% Na-β″-Al2O3 has good thermal stability at high temperatures.In (d), the glass transition temperature (Tg) of F127-NaClO4 is -46.2℃, the glass transition temperature (Tg) of F127-30%Al2O3 is -46.8℃, and the glass transition temperature (Tg) of F127-20%Na-β″-Al2O3 film is relatively left-shifted to -48.8℃. The lower Tg indicates that the chain bonds on the F127-20%Na-β″-Al2O3 electrolyte are more relaxed and relatively active at the working temperature, and there is no strong intermolecular interaction between the polymers, thereby improving the ionic conductivity.
[0065] Figure 7 (a) is the EIS spectra of Example 2, Comparative Example 2 and F127-30% Al2O3; (b) is the ionic conductivity of Example 2 and Comparative Example 2; (c) is the linear sweep voltammogram of Example 2, Comparative Example 2 and F127-30% Al2O3; (d) is the steady-state polarization curve of F127-20% Na-β″-Al2O3, and the inset is the Nyquist impedance spectrum of the Na / F127-20% Na-β″-Al2O3 / Na battery before and after polarization. It can be seen from the figure that in (b), within the content range of Na-β″-Al2O3 0 to 20%, the ionic conductivity of F127-Na-β″-Al2O3 increases with the gradual increase of the filler addition amount, and reaches a peak value when 20% Na-β″-Al2O3 is added, indicating that the addition of fillers can promote the free Na + As can be seen in (c), the electrochemical window of the CSE film does not change significantly after adding or not adding Na-β″-Al2O3, and remains at 4.7-4.9V without oxidation. Therefore, the F127-Na-β″-Al2O3 film is suitable for high-voltage positive electrodes. The polarization curves and impedance spectra of the F127-Na-β″-Al2O3 film before and after polarization after adding Na-β″-Al2O3 are shown in Figure 2. Figure 7 As shown in (d), the F127-Na-β″-Al2O3 film has an ion migration number of 0.77. The results show that the addition of Na-β″-Al2O3 helps to enhance the Na + Migration and ionic conductivity.
[0066] Figure 8(a) is the EIS curve of sodium vanadium phosphate (NVP) / electrolyte / Na battery prepared by Example 2, Comparative Example 2 and F127-30%Al2O3, (b) is the cycle performance of NVP / electrolyte / / Na battery prepared by Example 2, Comparative Example 2 and F127-30%Al2O3, (c) is the charge and discharge curve of NVP / F127-20%Na-β″-Al2O3 / Na battery, (d) is the rate performance curve of NVP / electrolyte / Na battery prepared by Example 2 and Comparative Example 2. As can be seen from the figure, (a) The impedance of the battery without Na-β″-Al2O3 filling is high, the impedance of the battery filled with Al2O3 is reduced, and the impedance of the battery filled with Na-β″-Al2O3 is sharply reduced. The ability to suppress sodium dendrites is a key issue in stabilizing the electrolyte / electrode interface. The initial specific capacity of the NVP / F127-NaClO4 / Na battery without power supply in (b) is similar to that after power supply, but the specific capacity decays rapidly with the increase of current density. The NVP / F127-Na-β″-Al2O3 / Na battery has good cycle performance with an initial specific capacity of 102 mAh·g -1 After 500 cycles of charge and discharge, the capacity retention rate is 95%. The rapid decay of F127 / NaClO4 / Na battery is related to the interface stability and the growth of sodium dendrites. (c) shows the change of discharge capacity of the battery at different current densities. Although the discharge capacity increases from 106 mAh g at 0.1C to 106 mAh g at 0.1C, the discharge capacity increases from 106 mAh g at 0.1C to 106 mAh g at 0.1C. -1 Reduced to 77mAh·g at 1C -1 , but the charge-discharge curves show a typical NVP electrode redox reaction platform. (d) At current densities of 0.1C, 0.2C, 0.3C, 0.5C and 1C, the discharge specific capacities are 107, 98, 92, 88 and 83 mAh·g, respectively. -1 , when cycled back to 0.1C, the specific capacity increases accordingly to the original value, indicating that the battery has good reversibility.
[0067] Fig. 9 (a) The constant current cycle curves of F127-NaClO4, F127-30% Al2O3 and F127-20% Na-β″-Al2O3 membrane Na symmetric batteries and the actual surface image of the sodium sheet after cycling, (b) is the critical current density test of F127-20% Na-β″-Al2O3 membrane Na symmetric battery when the current density is increased stepwise, (c) is the step size of the current increase of 0.05 mA cm -2 Symmetrical Na cell with F127-20% Na-β″-Al2O3 membrane at current density of 0.1 to 0.8 mA / cm 2Electrostatic cycle under the condition of . As can be seen from the figure, the constant current cycle curve in (a) can be used to characterize the stability of the electrolyte on sodium and the growth of sodium dendrites. It can be seen that due to the addition of Na-β″-Al2O3 filler, the growth of sodium dendrites in the solid electrolyte is greatly inhibited. Even after 800h, the current density is 0.1mA / cm 2 When the overpotential is less than 0.1V, the steady-state density also shows an overpotential of less than 0.1V. The solid electrolytes without fillers and with Al2O3 show obvious vibrations, reflecting lower stability. The attached figure is an enlarged view of some cycles in the constant current cycle. It can be seen that the voltage-time curve of the F127-Na-β″-Al2O3 battery is smoother and more stable than the voltage platform of the F127-NaClO4 and F127-30% Al2O3 batteries. In the actual picture, the surface of the sodium sheet looks uneven and has some holes. After the F127-Na-β″-Al2O3 with fillers is cycled for about 800h, it can be seen from the actual object that the sodium sheet after the cycle still has a metallic luster and a smooth surface, indicating that the addition of fillers inhibits the formation of sodium dendrites. The sodium stripping / electroplating ability at different current densities was tested using a Na / Na symmetric battery. As shown in (b) and (c), the maximum critical current density that the F127-Na-β″-Al2O3 film can withstand is 0.85mA / cm 2 .
[0068] It can be found from Example 2 and Comparative Examples 2-4 that the F127-Na-β″-Al2O3 composite solid electrolyte membrane was successfully prepared by combining the water-soluble polymer F127, sodium perchlorate and Na-β″-Al2O3. The entire preparation process is free of organic pollutants and is completed under a conventional atmosphere, making the solid electrolyte suitable for industrial applications. The electrochemical performance of the solid electrolyte was improved by introducing ion-conductive Na-β″-Al2O3 nanoparticle fillers. Na-β″-Al2O3 nanoparticles not only improve the ionic conductivity of the solid electrolyte by lowering the glass transition temperature (Tg) and releasing more free sodium ions, but also form a Na-Al-O solid electrolyte interface (SEI) due to the synergistic reaction of Na-β″-Al2O3 and NaClO4 with the sodium anode, which improves the interfacial stability of the electrolyte / sodium anode. The assembled NVP / CSE / Na battery can be cycled at different current densities of 0.1 to 1C and stably operate for more than 500 times at room temperature 0.3C. This composite solid electrolyte membrane has a good application prospect in future high-safety sodium batteries.
[0069] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0070] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a water-soluble polymer solid electrolyte, characterized in that the steps include: The water-soluble block polymer, metal salt and fast ion conductor are prepared into slurry, which is then coated on a porous fiber skeleton and dried to form a film to obtain the water-soluble polymer solid electrolyte.
2. The preparation method according to claim 1, characterized in that The water-soluble block polymer is an amphiphilic block copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene.
3. The preparation method according to claim 1, characterized in that: The metal salt is selected from one of lithium nitrate, sodium nitrate, lithium perchlorate, sodium perchlorate, lithium chloride and sodium chloride.
4. The preparation method according to claim 1, characterized in that: The fast ion conductor is selected from one of Li-β″-Al2O3 (LAO), Na-β″-Al2O3, LLZO and LAGP.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the water-soluble block polymer to the metal salt is 10:1-3; and / or, The mass ratio of the water-soluble block polymer to the fast ion conductor is 10:1-7; and / or, The solvent used in the slurry is water.
6. The preparation method according to claim 1, characterized in that: The drying and film-forming temperature is 60-120°C.
7. A water-soluble polymer solid electrolyte, characterized in that: The water-soluble polymer solid electrolyte is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the water-soluble polymer solid electrolyte as claimed in claim 7 in a solid-state battery.
9. The use according to claim 8, characterized in that The solid-state battery is a solid-state lithium battery or a solid-state sodium battery.
10. An electrochemical device, characterized in that: The electrochemical device comprises the water-soluble polymer solid electrolyte according to claim 7.
Citation Information
Patent Citations
Pluronic segmented copolymer based hydrogel electrolyte and application thereof
CN106785029A
Composite all-solid-state polymer electrolyte and preparation method thereof
CN111509296A
Electrolyte matrix as well as preparation method and application thereof
CN112687949A
Plasticizer-free segmented copolymer solid electrolyte as well as preparation method and application thereof
CN114976269A
Composite solid electrolyte membrane and preparation method thereof
CN116130748A
Cited By
High-voltage-resistant polymer solid electrolyte, preparation method thereof and high-voltage all-solid-state sodium battery
CN120978190A